2022
DOI: 10.1111/dar.13513
|View full text |Cite
|
Sign up to set email alerts
|

Substance use in the emergency department: Screening for risky drug use, using the ASSIST‐Lite

Abstract: Introduction: Substance use is a common contributing factor to emergency department (ED) presentations. While screening, brief intervention, and referral to treatment for alcohol and tobacco is common in ED settings, it is not routinely conducted for illicit substances. This study aimed to deploy the ASSIST-Lite to screen for risky use of alcohol and other drugs in the ED, to identify differences in risk based on between demographic characteristics.Method: All ED attenders, aged 18 years or older, deemed well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The training will be accredited for professional development hours, and will consist of two sessions, each lasting approximately 60 minutes each. These will follow the format previously used in an implementation study of ASSIST-Lite in the Emergency Department of a large metropolitan health service [27]. The training will be tailored to address any gaps identified through phase 2.…”
Section: Training Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The training will be accredited for professional development hours, and will consist of two sessions, each lasting approximately 60 minutes each. These will follow the format previously used in an implementation study of ASSIST-Lite in the Emergency Department of a large metropolitan health service [27]. The training will be tailored to address any gaps identified through phase 2.…”
Section: Training Interventionmentioning
confidence: 99%
“…ASSIST-Lite is a tablet-based screening tool which quantifies risk of harm for a range of common substances, and can guide brief advice or facilitate active referral depending on the level of risk [26]. Although ASSIST-Lite was designed, and has been validated, for use in time-critical areas (e.g., emergency departments) [26,27] to our knowledge it has not been validated for use amongst pregnant women. Despite this lack of evaluation in the antenatal setting, ASSIST-Lite is currently included in the standardised antenatal assessment at one of the largest metropolitan tertiary referral centres in South Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Detection and intervention during the primary health care consultation may prevent the progression of many of these cases. A recent study at an Australian hospital emergency department found almost 40% of individuals attending the emergency department were screened as being at moderate risk for a single substance; pointing to a potential missed opportunity for SBIRT at prior settings (Stevens et al 2022). Although this may be due to a variety of reasons, it highlights the importance of building capacity of the primary health care workforce to confidently and capably deliver a brief intervention for substance use disorders in terms of prevention of future harm.…”
Section: Introductionmentioning
confidence: 99%
“…SBIRT programs seek to rapidly assess the severity of problematic drug or alcohol use, and then provide either feedback and education regarding risk, a brief intervention or referral to formal treatment depending on the severity of the problem. SBIRT programs have been found to be clinically and economically effective in relation to SUDs (515,516) but are rarely applied in emergency settings (other than for problem drinking) (517).…”
Section: Experimental Trialling Of Sbirt Utilising Act Components For...mentioning
confidence: 99%